The Educational Productivity Paradox. - Peslak, Alan R. (Communications of the ACM, 2005)
The article cites some studies which researched the effects of increased IT expenditures in educational institutions. In recent years large expenditures have been made in IT in educational institutions with little corresponding study of whether there have been productivity gains in the form of better educated students associated with these expenditures. The study "The Productivity Paradox of Information Technology," conducted by E. Brynjolfsson and published in the December 1993 issue of the journal "Communications of the ACM," studied labor and commerce statistics and found that IT investments did not result in productivity gains. It found that there was a negative relationship between output per hour and IT spending. One of the significant articles on the association between computers and school performance, "Computers and School Performance," was conducted by P. Attewell and J. Home Battle and was published in a 1999 issue of the journal "The Information Society." The study reviewed the effects of home computers on standardized test scores in reading and mathematics, as well as a self-report on grades.